3 - Information and Communication Technology (ICT) Use and Research Productivity of Middle-level Lecturers in Nigerian Universities - John Lekan Oyefara; Pius Adejoh; Waziri B. Adisa; Khadeejah Adebisi Abdulsalam; Tunde Alabi (Journal of Higher Education in Africa, 2026)
This article examines the influence of the availability and use of information and communications technology (ICT) on the research outputs of middle-level lecturers in Nigerian universities. The influence of specific variables such as the availability of a functional research laboratory, swift internet connectivity, functional laptop computers, functional e-library and data analysis/simulation software was investigated. Performance in research output was operationalised to mean the number and quality of publications. The study utilised a non-experimental research design involving the triangulation of a cross-sectional survey and in-depth interview research methods. The cross-sectional survey method was used to elicit quantitative data from 1,325 respondents drawn from 12 universities in South-west Nigeria, while in-depth interviews with administrators, unit managers, heads of departments, lecturers and students were conducted to generate qualitative data for the study. The results show that while ICT facilities were largely available, ownership was mostly personal; and that although access to ICT impacts research output, productivity of middle-level lecturers in this regard is impaired by inadequate underlying infrastructure and poor funding support for publication and higher education more generally. The article recognises the role of middle-level academics in the domestication of ICT-based higher education in Nigeria and calls for improved funding and more aggressive integration of ICT in higher education in the country.